Segmentation Data for Nigeria and India States of Bihar, Odisha, and Uttar Pradesh - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
This dataset was compiled by processing and harmonizing multiple secondary datasets, covering Nigeria and three states in India (Bihar, Odisha, and Uttar Pradesh), to help those working in the agricultural development sector identify and characterize groups of smallholder farmers that have the highest potential leverage in terms of increasing agricultural productivity. The dataset includes multiple various covering the agricultural production constraints, opportunities, and gender issues of the identified groups, aiming to fill a data gap in the understanding of the context at the farm level and how that affects what types of technologies, practices, or services are needed.